Thermo-economic analysis and optimization of a zoetropic fluid organic Rankine cycle with liquid-vapor separation during condensation. (15th September 2017) - Luo, Xianglong; Liang, Zhihui; Guo, Guiqi; Wang, Chao; Chen, Ying; Ponce-Ortega, José María; El-Halwagi, Mahmoud M.
Highlights: A zeotropic fluid ORC with liquid separation during condensation is proposed. Mathematical analysis and optimization models of the proposed ORC are formulated. A case study is presented to demonstrate the zeotropic ORC with liquid-separation. The influences of key parameters on the cycle performance are conducted. Abstract: Organic Rankine cycle (ORC) is a promising thermal-to-power technology that uses low-temperature heat from various sources including renewable energy and waste heat. A zeotropic fluid ORC offers thermodynamic-performance advantages over pure fluid ORC because of the relatively low irreversibility during the heat transfer process. Nonetheless, zeotropic fluid ORC may incur higher cost than pure fluid ORC because the former has high mass transfer resistance and small temperature difference in the heat exchanger. Limited research has been carried out to enhance thermo-economic performance of zeotropic ORC. In the present study, an ORC that uses zeotropic fluids and undergoes liquid–vapor separation during condensation is proposed. A thermo-economic analysis is developed based on a new optimization model for the proposed ORC. The objective function of the optimization model is the minimization of the specific investment cost. A genetic algorithm is used to solve the optimization model. A case study is then solved to illustrate the advantages of the proposed ORC and validate the proposed thermo-economic optimization method. The results of the thermodynamic analysis show that the condenser area of the proposed ORC is 17.6% lower than that of the conventional ORC under the same working conditions. Thermo-economic optimization results show that the specific investment cost of the proposed ORC is 13.3–18.4% lower than that of the basic ORC. Meanwhile, the second law efficiency of the proposed ORC is 4.2% higher than that of the conventional ORC. A sensitivity analysis is carried out to assess the dependence of the ORC performance on the temperatures of the heat source and the surrounding environment.